Handgrip Strength and Mortality in Elderly Koreans: Evidence From the Korea Longitudinal Study of Ageing - Kim, Keuntae; Ho, Jeong Hwa (Asia-Pacific Journal of Public Health, 2020)
Despite substantial research on numerous aspects of health in the elderly, past studies that examined the association between handgrip strength and mortality have been conducted with samples drawn mostly from Caucasian populations, and little is known about whether similar trends are found in non-Western contexts such as Korea. The present study drew data from KLoSA (Korean Longitudinal Study of Aging), a nationally representative sample of middle-aged adults, and followed up for a decade. Results from discrete-time event history analysis of mortality indicated that higher handgrip strength significantly reduces the likelihood of death in both men and women. Men in the highest third of handgrip strength were 53.9% less likely to experience death than those in the lowest third. Women followed a similar pattern: middle and high handgrip strength reduced the odds by 26.4% and 48.3%, respectively. These findings suggest that handgrip strength has a significant impact on elderly mortality and does so in a negatively gradient manner.
Keywords: Aged; Female; Hand Strength; Humans; Longitudinal Studies; Male; Mortality; Republic of Korea; discrete-time event history analysis; handgrip strength; KLoSA; Korea; mortality